3D stereoscopic visualization in the evaluation of fenestrated endovascular repair of abdominal aortic aneurysms - Sun, Zhonghua; Squelch, Andrew; Allen, Yvonne (RSNA, 2008)
The purpose of the study was to explore the application of 3D stereoscopic visualization in the evaluation of patients with abdominal aortic aneurysm treated with fenestrated endovascular grafts.